HISTCONGO: EDUCATIONAL APPLICATION ABOUT THE DEMOCRATIC REPUBLIC OF CONGO - Ribeiro Tchinhama, Laurindo Paulo [UNESP]; Silva, Fernanda de Paula; Saint Pierre, Hector Luis [UNESP]; Milagre, Selma Terezinha (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2021)
The article presents the development of a mobile application for teaching and research on the Democratic Republic of Congo, named: HistCongo (RDC/Kinshasa). The development aimed to disseminate knowledge about the country through information and historical data in an interactive and accessible way, to democratize the process of teaching and learning about African countries. It is noted that, of the existing applications, few seek to foster teaching, research, and democratization of knowledge about African culture, in particular, this country of historical magnitude. For this purpose, analyses and information selections was made from specialized literature in the technological and political-historical area, as well as search for applications with the same purpose. As a result, the HistCongo mobile application was created and made available to the public with relevant information and data to facilitate the democratization of research, teaching, and learning. With this tool, we seek to contribute to Distance Education (EaD) in Brazil, in an accessible way, through mobile devices.
Keywords: democratic republic of congo; mobile application; teaching and learning; distance education